Associations between estimated glucose disposal rate and arterial stiffness and mortality among US adults with non-alcoholic fatty liver disease - Song, Junting; Ma, Ruicong; Yin, Lin (Frontiers in Endocrinology, 2024)
Background: The estimated glucose disposal rate (eGDR), an effective indicator of insulin resistance, has been related to acute coronary syndrome, ischemic stroke and heart failure. This study aims to explore the relationship between eGDR and arterial stiffness, all-cause mortality and cardiovascular mortality in patients with non-alcoholic fatty liver disease (NAFLD).Methods: Participants with NAFLD were chosen from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2018. The main outcomes are arterial stiffness (represented by estimated pulse wave velocity, ePWV), all-cause and cardiovascular mortality. Multiple cox regression models, restricted cubic spline, sensitivity analysis and subgroup analysis were carried out to investigate the correlation between the insulin resistance indicators and mortality and arterial stiffness.Furthermore, receiver operating characteristic curves were used to compare the predictive value of the eGDR with the triglyceride-glucose (TyG) index and the homeostasis model assessment of insulin resistance (HOMA-IR) for all-cause and cardiovascular mortality.In this study, a total of 4,861 participants were included for analysis. After adjusting confounding factors in the multivariate weighted cox regression model, the eGDR was inversely associated with the all-cause mortality (Q4 vs. Q1, HR =0.65 (0.48-0.89, P=0.01) and cardiovascular mortality (Q4 vs. Q1, HR =0.35 (0.19-0.65, P<0.001). Compared with TyG index and HOMA-IR, the eGDR shows excellent predictive value in all-cause mortality (0.588 vs. 0.550 vs. 0.513, P < 0.001) and cardiovascular mortality (0.625 vs. 0.553 vs. 0.537, P < 0.001). In addition, we found a significant negative correlation between eGDR and arterial stiffness (β=-0.13(-0.14--0.11, P< 0.001). However, TyG index and HOMA-IR showed no significant correlation to arterial stiffness.Low eGDR (an indicator of insulin resistance) levels are related to an increased risk of arterial stiffness and mortality in NAFLD patients in the United States.